LANGUAGE EDUCATION AS LITERACY EDUCATION: IMPROVING INDIVIDUAL INTELLIGENCES THROUGH LANGUAGE TEACHING AND LEARNING - Iis Nur Rodliyah, M.Ed (ISSN)
The fact shows that language education closely related to literacy education results in the ability to read and write at a designated level of proficiency. Literacy is also defined as a technical capability to decode or reproduce written or printed signs, symbols, or letters combined into words. However, it has become increasingly common to refer to different forms of literacy, such as computer, mathematical, or graphic literacy. Considering the common techniques used in language teaching, they may contribute to the improvement of the students’ ability in both the basic literacy and functional literacy (i.e. some skill in reading and writing; and the ability to read, write, and calculate figures well enough to carry out activities that many people consider necessary to function in society, respectively). Here, we can notify that functional literacy refers to individual ability in surviving life which also serves as reflection of individual multiple intelligences covering several areas that can be developed over a lifetime. This paper invites the reader to recall several techniques in teaching languages which can also function as the techniques of improving literacy-both basic and functional literacy. In language teaching, the use of, for example, puzzles and games, classification and categorization will lead to logical competence; chart and grids, videos, and drawing will lead to visual/spatial intelligence; hands-on activities and pantomime will lead to body/kinesthetic intelligence; singing and jazz chants will lead to musical/rhythmic intelligence; pair-work and group problem solving will lead to interpersonal intelligence; journal keeping will lead to intrapersonal intelligence; and note-taking, story telling and debates will lead to verbal/linguistic intelligence.